STRATEGIES OF GUIDANCE AND COUNSELING TEACHERS TO OVERCOME TIME LIMITATIONS IN CLASS ENTRY - Rawi, Hafizah Wichayani; Tambusai, Khairuddin (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This research aims to describe the strategies used by Guidance and Counseling teachers in addressing time limitations in classroom entry at SMA Dharma Utama. Time limitations have become one of the significant challenges in implementing services, particularly in providing equitable attention to all students. This study uses a qualitative approach with a case study method. The subjects of the research are teachers and several students, as well as relevant subject teachers. Data collection techniques were conducted through in-depth interviews, observations, and documentation. The results of the study indicate that the Guidance and Counseling teachers apply various strategies such as utilizing digital technology (social media, class WhatsApp groups), flexible service implementation outside of class hours, and collaboration with homeroom teachers and subject teachers. In addition, guidance and counseling teachers also optimize group guidance and schedule classical counseling services. These strategies have proven to be quite effective in reaching students more broadly despite time constraints. This research recommends the need for stronger institutional support and the integration of guidance and counseling programs with other school activities to improve the effectiveness of guidance and counseling services in the future.